2015
DOI: 10.5194/bg-12-4637-2015
|View full text |Cite
|
Sign up to set email alerts
|

Vertical partitioning and controlling factors of gradient-based soil carbon dioxide fluxes in two contrasted soil profiles along a loamy hillslope

Abstract: Abstract. In this study we aim to elucidate the role of physical conditions and gas transfer mechanism along soil profiles in the decomposition and storage of soil organic carbon (OC) in subsoil layers. We use a qualitative approach showing the temporal evolution and the vertical profile description of CO 2 fluxes and abiotic variables. We assessed soil CO 2 fluxes throughout two contrasted soil profiles (i.e. summit and footslope positions) along a hillslope in the central loess belt of Belgium. We measured t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
(79 reference statements)
1
12
0
Order By: Relevance
“…Relatively inconsistent views about the effect of soil redistribution on the spatial variability of CO 2 effluxes exist. Some studies reported higher respiration rates at footslope positions relative to summit and shoulder positions (Reicosky et al 2005;Webster et al 2008;Wiaux et al 2015), but opposite trends were also observed in some regions (Epron et al 2006;Wei et al 2014;Zhang et al 2016).…”
Section: Controls On Soil Surface Respiration Fluxesmentioning
confidence: 96%
See 1 more Smart Citation
“…Relatively inconsistent views about the effect of soil redistribution on the spatial variability of CO 2 effluxes exist. Some studies reported higher respiration rates at footslope positions relative to summit and shoulder positions (Reicosky et al 2005;Webster et al 2008;Wiaux et al 2015), but opposite trends were also observed in some regions (Epron et al 2006;Wei et al 2014;Zhang et al 2016).…”
Section: Controls On Soil Surface Respiration Fluxesmentioning
confidence: 96%
“…These results support that the SOC at such a footslope is stored along the soil profile and involved in a long-term stabilization process and simultaneously support that the depositional profile emits more CO 2 than the summit due to its high amount and quality of SOC. Wiaux et al (2015) reported that in crop soils, approximately 90 to 95% of the fluxes originated from the first 10 cm of the soil profile at the footslope, while at the summit, the first 30 cm of the soil profile significantly contributed to surface fluxes. These results suggest that the depositional topsoil SOC is prone to be mineralized, and the SOC in this depositional context is stabilized at subsoil depth.…”
Section: Controls On Soil Surface Respiration Fluxesmentioning
confidence: 99%
“…Location within the relief also to a large extent defines the soil profile structure. The research of Wiaux [15] showed that carbon dioxide excretion from a soil profile at the peak of a loess hill significantly differs from that at the foot of the hill. This was evidently due to differences in the thermal-humidity conditions, in both the surface and deeper horizons.…”
Section: Introductionmentioning
confidence: 99%
“…This was evidently due to differences in the thermal-humidity conditions, in both the surface and deeper horizons. The investigations of Wiaux [15] primarily concerned CO 2 excretion from the soil surface, but measurements carried out at different depths showed how the physical characteristics of every soil horizon can impact the intensity of CO 2 excretion.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with basic soil properties (e.g., soil texture, porosity), direct information on O 2 and/or CO 2 concentrations has been determined to be more sensitive for the evaluation of soil aeration and respiration (Klimanek and Greilick, 1981;Ben-Noah and Friedman, 2018). Direct measurements of soil gas concentrations can thus be highly valuable to improve our mechanistic understanding of biological soil processes and their interaction with physical soil properties Šimůnek and Suarez, 1993;Risk et al, 2002;Hashimoto and Komatsu, 2006;Taneva et al, 2006;Riveros-Iregui et al, 2007;Blagodatsky and Smith, 2012;Wiaux et al, 2015). Direct measurements of CO 2 concentrations, together with modeled or estimated diffusivity, provide direct information on depth-dependent respiration and flux as implemented in the soil-CO 2 profile method (Risk et al, 2002;Hirano et al, 2003;Pumpanen et al, 2003a;Tang et al, 2003;DeSutter et al, 2008;Han et al, 2014;Xiao et al, 2015;Wiaux et al, 2015).…”
mentioning
confidence: 99%